Communication Experience of Indonesian Migrant Workers' Children in the Process of Building Self Concept in Sampang District - Moh. Afdol (Green Publisher Indonesia, 2026)
This research aims to explore the communication experiences of children of Indonesian migrant workers (TKI) in Sampang Regency and how these experiences shape their self-concept amid the absence of parental presence. Using a qualitative descriptive approach, the research employed in-depth interviews and light participant observation with five informants aged 13–25 years. The findings reveal that communication between TKI parents and their children occurs infrequently and tends to be practical, focusing on material needs rather than emotional affection. This condition creates ambivalence in self-concept formation, where children feel proud of their parents' economic success yet experience emotional emptiness. Moreover, the social environment strongly influences this process through the